Memudarnya Peranan Baya Muli Mekhanai Pada Perkawinan Masyarakat Lampung Saibatin - Yessi Parisca; Risma Margaretha Sinaga; Muhammad Basri (University of Lampung, 2021)
Abstract: The Fading Of Baya Muli Mekhanai Role Saibatin Lampung Community Marriage. This study aims to determine the youthful role of baya muli mekhanai in the marriage of the people of Lampung Saibatin and the factors that influence it in Pekon Way Suluh, Krui Selatan District, Pesisir Barat Regency. The method used is descriptive method. The results of this study are the fading of the role of baya muli mekhanai seen from the low intensity of the role of baya muli mekhanai today and it is caused by factors of changes in lifestyle and technological developments. Key words: waning, role of mulimekhanai, marriage.